Leaf traits and herbivory in a resin-producing plant species growing in floodable and non-floodable areas of the pre-Amazonian white-sand forest - de Araújo Rodrigues, Maria Ivanilde [UNESP]; Santos, Elza Maria Guimarães [UNESP]; de Nicolai, Juan [UNESP]; Rodrigues, Tatiane Maria [UNESP] (FapUNIFESP (SciELO), 2024)
Plant species in the white-sandy forests are subject to unstable soils, high salinity, luminosity, extreme temperatures, and flooding caused by tidal cycles. Protium heptaphyllum, a tree species in the Burseraceae family known for its resin production, occurs in both floodable and non-floodable areas. We investigated differences in the accumulated herbivory indexes in leaves during the leaflet lifespan and correlated these data with leaf morphoanatomical traits in plants from floodable and non-floodable areas. Samples of young and mature leaves were processed using standard plant anatomy techniques. The percentage of leaf area consumed by herbivores and quantitative morphoanatomical data were subjected to MANOVA and ANOVA. Herbivory indexes of young and mature leaves were similar between plants from floodable and non-floodable areas. The morphoanatomical features of young leaves were also similar in plants from both areas. However, mature leaves from individuals in the floodable area exhibited longer leaflets and a higher abundance of wider secretory canals compared to plants from the non-floodable area. We suggest that most leaf consumption by herbivores occurs during the early stages of leaf development when there are fewer chemical defenses, and the leaflets are more tender.
Keywords: anatomy; flooding; herbivory; leaf; restinga; “breu-branco”